Hubungan Antara Resiliensi Akademik dan Dukungan Sosial Terhadap Stress Akademik Mahasiswa Perantau di Universitas Negeri Malang - Adjie Satrio Ambawani; Nur Hidayah (Pro Panoramic Solution, 2025)
This study aims to examine the relationship between academic resilience and social support with academic stress among migrant students at Universitas Negeri Malang. The research employed a descriptive correlational design. The population of this study consisted of migrant students at Universitas Negeri Malang, with a sample of 175 respondents selected using a simple random sampling technique. Data were collected using standardized scales. Data analysis was conducted through descriptive analysis and correlational analysis using the Pearson Product Moment correlation test, as well as multiple linear regression analysis. The results of the correlational analysis indicated that academic resilience was negatively and significantly correlated with academic stress (r = −0.990; p < 0.01).